Ethical evaluation of labour union strikes in Nigeria and the religious value of the dignity of labour (2021)
Agitations by labour unions in the country have become a recurring decimal and this has led to a series of arrests and death of members in the course of fighting for their legitimate rights of improved welfare packages. In this incessant face- off between government and labour unions in the country, many scholars have written voicing the opinions. While some blamed successive government on their insensitivity to the plight of Nigerian workers, others condemned the actions of workers as falling below expectation as many are inefficient and incompetent. But, an area where attention has not been focused on, has to do with the value of dignity of labour among the Nigerian workforce. It is therefore pertinent to take a critical look at the religious value of the dignity of labour vis - a - vis the attitudes of those in the corridors of power and the plight of workers who are the fulcrum on which the economy upon which any nation stands. It is in light of this that this paper will examine among other things, strike actions in Nigeria, and the meaning of ‘dignity of labour’ from a religious perspective. Lastly, a clarion call will be made on stakeholders in labour matters on the need to address the lingering gridlock between government and labour unions in the country in order for the efforts of the present administration at revamping the economy not to be a mere waste of time